Problems of development of social entrepreneurship in the Republic of Kazakhstan: solutions and tools - Gelashvili, N.N.; Orynbassarova, Y.D.; Zhumanova, B.K. (KSU Publ., 2019)
In article problems of development of social business in Kazakhstan taking into account tendencies of modern economy in which the significant role is played by various business models are considered. Social business in Kazakhstan can be considered new the direction of development of social policy in the state. In too time experience of foreign countries proves high efficiency of realization of social policy in the country by means of social business. In article basic barriers of development of social business are considered. It is proved that now social business in Kazakhstan develops in the traditional directions of service economy. And it substantially limits possibilities of further development of social business. To thereby become relevant search new by method of overcoming barriers in development of social business. And here the business models based on realization of nonconventional approaches in the organization of work can be of great importance. Search of financing of social projects remains a key problem. In article possible alternative ways of search of financing of social projects, besides traditional sources are considered.
Қазақстан Республикасындағы əлеуметтік кəсіпкерліктің даму мəселелері: шешімдері мен құралдары
Проблемы развития социального предпринимательства в Республике Казахстан: пути решения и инструменты
Keywords: social business; non-profit organizations; monetization of social projects; socially responsible business; business model; crowd funding